Skin disinfection in preterm infants. Issue 3 (September 1993) - Malathi, I; Millar, M R; Leeming, J P; Hedges, A; Marlow, N
Abstract : Greater care and a more thorough approach to intravenous catheter site disinfection may be important for the prevention of catheter related sepsis, especially with coagulase negative staphylocci in preterm infants. The efficacy of skin disinfection was evaluated in preterm infants using a skin swabbing technique after disinfectant exposure. In the first part of the study, 25 peripheral intravascular catheter sites were quantitatively sampled immediately after routine cannula insertion. Bacterial counts greater than 100 colony forming units/cm2 were observed from 10 (40%) sites. In the second part, sampling for bacterial colony counts was done after skin cleansing with various durations of exposure of chlorhexidine/alcohol swabs or povidone iodine. The overall mean reduction in bacterial colony counts after skin cleansing ranged from 90-99%. Skin sterilisation was achieved in 33-92% of cases. The use of two consecutive 10 second exposures resulted in a significantly improved reduction in colony counts compared with a single 10 second wipe. A longer 30 second exposure also resulted in a greater reduction of bacterial numbers compared with a shorter duration of 5 or 10 seconds. Repopulation of disinfected sites occurred within 48 hours. This effect was delayed by occluding the cleansed site with a semipermeable dressing. There were no significant differences between povidone iodine and the chlorhexidine swabs in reducing bacterial numbers. This study has demonstrated that a brief exposure with a premoistened disinfectant swab is not sufficient for complete elimination of resident skin flora of newborn infants. The use of two consecutive cleanings, or a longer duration of cleansing is recommended for more effective skin sterilisation.